2014
DOI: 10.1080/00071668.2013.864380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymorphisms and haplotypes within theMSTNgene on duck growth trait

Abstract: 1. Polymorphisms of the duck MSTN gene were investigated in 413 individuals by DNA sequencing and polymerase chain reaction restriction fragment length polymorphism. Four single nucleotide polymorphisms (G129A, C324T, A981G and C1002A), with A981G and C1002A completely linked, were found in the coding region. 2. Association analysis showed that different genotypes of all the identified SNPs were significantly associated with duck growth rate from week 5, 6 and 2 for G129A, C324T and A981G (C1002A), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As already mentioned, some duck genome regions determining some performance traits have been identified. Gong et al (2014) found significant effects of three polymorphisms within the MSTN gene on body weight of duck in consecutive weeks of age (from 5 to 11 weeks), whereas no effects have been estimated for younger birds. Furthermore, Zhao et al (2015) detected significant associations between the VLDLR gene (for four diplotypes) and body weight at 10 weeks in Gaoyou domestic duck breed.…”
Section: Successful Identification Of Duck Genome Region Determining mentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, some duck genome regions determining some performance traits have been identified. Gong et al (2014) found significant effects of three polymorphisms within the MSTN gene on body weight of duck in consecutive weeks of age (from 5 to 11 weeks), whereas no effects have been estimated for younger birds. Furthermore, Zhao et al (2015) detected significant associations between the VLDLR gene (for four diplotypes) and body weight at 10 weeks in Gaoyou domestic duck breed.…”
Section: Successful Identification Of Duck Genome Region Determining mentioning
confidence: 99%
“…Therefore, the analysis of the association between Anas platyrhynchos the genome and phenotypes is still limited. However, over the last decades a number of studies on the associations of single loci with performance traits of ducks (Huang et al, 2005(Huang et al, , 2006Maak et al, 2000;Wu et al, 2008;Gong et al, 2014;Mucha et al, 2014b), using different methodological approaches, have been published. Generally, they focus on single measures per individual.…”
Section: Successful Identification Of Duck Genome Region Determining mentioning
confidence: 99%
“…In this regard, Xu et al (2013) found that gene frequencies of A and B alleles were 0.53 and 0.47, respectively at three mutated sites (T126 C, T 708 C and T 952 C) of MSTN gene in ducks. In addition, in a study of the MSTN polymorphisms in (White Liancheng ˣ Whit Kaiya) duck cross (Gong et al, 2014) the results showed frequencies (0.31 and 0.69) for G and A alleles, respectively at G 129 A SNP site of exon1 of MSTN gene, while frequencies of T and C alleles were 0.39 and 0.61, respectively at C324T SNP site of exon2 of MSTN gene. In chickens, Paswan et al (2014) found that frequency of A allele was higher (0.76) than that of B allele (0.24).…”
Section: Polymorphism Of Mstn Genementioning
confidence: 97%
“…A number of studies by different researchers (Zhang et al, 2011;Paswan et al, 2014) reported that genetic polymorphisms of the MSTN gene have many effects on productive traits such as body weight, weight gain, carcasses specifications and reproductive efficiency. Respecting studies on ducks (Lu et al, 2011 ;Gong et al, 2014) found different effects of MSTN gene mutations on body weights at different ages, explaining that the nitrogen base change due to genetic mutation may alter an amino acid that has an effect on body weight during the growth phase. Thus, the MSTN gene could be considered as primarily responsible for muscle development and could be a potential candidate gene for muscle growth-genetic analysis.…”
Section: Introductionmentioning
confidence: 99%